Promoting HIV Testing for Gay and Bisexual Men: An Evaluation of the 2011-2012 Campaign in Toronto and Ottawa. Issue 1 (January 2016) - Adam, Barry D.; Gardner, Sandra; Major, Carol; Campbell, Diana; Light, Lucia; Globerman, Jason
This article reports on a social marketing campaign directed toward high-risk men who have sex with men in Toronto and Ottawa to encourage testing for HIV and syphilis; improve knowledge about HIV transmission, seroconversion symptoms, and the HIV window period; and heighten awareness of syphilis transmission and its relationship to facilitating HIV transmission. Evaluation data were collected from a large-scale online pre-and postcampaign survey of sexually active men who have sex with men and from laboratory testing data. Men who turned up to be tested also filled out an exit survey. The campaign websites attracted some 15, 000 unique visitors, 54% of whom had an IP address in Toronto or Ottawa. Laboratory data showed a 20% increase in HIV testing in Toronto over the campaign compared to the previous year. The overall rate of HIV-positive tests remained relatively constant. Knowledge levels about seroconversion symptoms, sexually transmitted infection and HIV transmission, and the HIV window period were significantly better among postcampaign survey respondents aware of the campaign compared to postcampaign respondents who were not aware and compared to precampaign respondents.